On Reliability Approach for Testing of Many Distributions for Pair of Markov Chains - Haroutunian, Evgueni; Grigoryan, Naira (Mathematical Problems of Computer Science, 2021)
The problem of three hypotheses logarithmical asymptotically optimal testing for a pair of simple homogeneous stationary Markov chains is examined. It is supposed that M probability distributions are known and each of Markov chains independently of other follows to one of them. The matrix of all error probability exponents (reliabilities) is studied.